Cryptographic Strain‐Dependent Light Pattern Generators. Issue 1 (19th October 2021) - D'Elia, Francesca; Pisani, Francesco; Tredicucci, Alessandro; Pisignano, Dario; Camposeo, Andrea
Abstract: Refractive freeform components are becoming increasingly relevant for generating controlled patterns of light, because of their capability to spatially modulate optical signals with high efficiency and low background. However, the use of these devices is still limited by difficulties in manufacturing macroscopic elements with complex, 3D surface reliefs. Here, 3D‐printed and stretchable magic windows generating light patterns by refraction are introduced. The shape and, consequently, the light texture achieved can be changed through controlled device strain. Cryptographic magic windows are demonstrated through exemplary light patterns, including micro‐QR‐codes, that are correctly projected and recognized upon strain gating while remaining cryptic for as‐produced devices. The light pattern of micro‐QR‐codes can also be projected by two coupled magic windows, with one of them acting as the decryption key. Such novel, freeform elements with 3D shape and tailored functionalities is relevant for applications in illumination design, smart labels, anti‐counterfeiting systems, and cryptographic communication. Abstract : Flexible, 3D‐printed magic windows capable of generating complex light patterns are introduced. Their capability as cryptographic labels is demonstrated by encrypting the information encoded in micro‐QR‐codes into stretchable topographies. The information can be retrieved and made decipherable by low‐cost QR scanners, upon applying a calibrated uniaxial strain.